Resistive switching characteristics of methyl-ammonium lead iodide perovskite during atmosphere degradation - Wafee, Seema; Leu, Ching-Chich; Chen, Yu-Wen; Liu, Bernard Haochih (Journal of alloys and compounds, 2023)
Methylammonium lead iodide (MAPbI3) with extraordinary optoelectronic properties has recently been explored for memristors. Despite significant studies on its susceptibility to air, there has been limited attention towards the impact of ambiance on resistive switching (RS), specifically, the nanoscale electrical properties of interest. We used scanning probe microscopy (SPM) to study local current-voltage (I-V) characteristics, time-scale evolution of hysteresis, current maps, and topography to profoundly understand the ambient degradation. The local and macroscopic current-voltage characteristics are studied by interface modulation with (3-Aminopropyl)trimethoxysilane (APTMS) in devices, i.e., ITO/APTMS/MAPbI3 and ITO/ MAPbI3/APTMS. We report three stages of degradation based on quantitative nano-mechanical (QNM) characterizations and local I-V properties: stage 1 comprising of increased Young’s modulus accompanied by the appearance of hysteresis; stage 2 with decreased Young’s modulus when RS and negative differential resistance (NDR) happen with the evolution of lead iodide (PbI2); stage 3 when RS disappears with enhanced Young’s modulus and densification of PbI2. The enhanced nanoscale and macroscale RS characteristics of ITO/MAPBI3 and ITO/APTMS/MAPbI3 could be attributed to the humidity-induced degradation of MAPbI3 into PbI2 indicated by XRD. These characteristics at the nanoscale however diminish on Day 7 showing the nano-scale RS devices requires the prompt attention of researchers. [Display omitted] •CH3NH3PbI3 perovskite degradation was examined daily until day 7 in ambient conditions for the resistive random access memory (RRAM) device.•(3-Aminopropyl)trimethoxysilane (APTMS) was employed as a passivating layer.•Structural alteration, electric current maps, local current-voltage curves, and Young’s modulus variation were studied.•The On/Off ratio of the devices in the ambient increases initially but fades away by day 7.